The Role of Hyaluronan Treatment in Intestinal Innate Host Defense - Kim, Yeojung; de la Motte, Carol A. (Frontiers in Immunology, 2020)
Hyaluronan (HA) is best known as an abundantly present extracellular matrix component found throughout the body of all vertebrates, including humans. Recent evidence, however, has demonstrated benefits of providing HA exogenously as a therapeutic modality for several medical conditions. Here we discuss the effects of providing HA treatment to increase innate host defense of the intestine, elucidate the size specific effects of HA, and discuss the role of various HA receptors as potential mediators of the HA effects in the intestine. This review especially focuses on HA interaction with the epithelium because it is the primary cellular barrier of the intestine and these cell play a critical balancing role between allowing water and nutrient absorption while excluding microbes and harmful dietary metabolites that are constantly in that organ’s environment.